Clinical and laboratory aspects of histoplasmosis: a bibliographic review (Research, Society and Development, 2020)
Histoplasmosis is a systemic mycosis, endemic, of worldwide distribution, which is caused by inhaling the propagules of Histoplasma capsulatum, in which they lodge in the lungs and subsequently trigger the human infection that can spread through the body. The forms of clinical manifestations vary according to the degree of impairment of the immune system of the individual. Therefore, the present study aims to describe the clinical and laboratory aspects of Histoplasmosis, by understanding that, today, errors still occur when identifying this mycosis, which leads to the increase of mortality, so early diagnosis is essential for the quality of life of the individuals. The study was based on a bibliographic review, with a qualitative approach, of an exploratory type. Because Histoplasmosis is an opportunistic mycosis, capable of affecting different organs and tissues, better training of professionals is necessary, associated with the application of the correct diagnostic techniques. Thus, it is concluded that the diagnosis made through laboratory techniques, such as the mycological, serological, histopathological, molecular examination, are fundamental for the early and correct diagnosis of the individual, which will contribute to improve therapeutic action.